ACADEMIC PROCRASTINATION AMONG ENGLISH MASTER STUDENTS: THE LEVEL, AREAS AND REASONS - Annisaq Annisaq; Fadly Azhar; Supriusman Supriusman (Prodi Administrasi Pendidikan Program Pascasarjana Universitas Riau, 2025)
Academic procrastination is a persistent challenge in higher education, particularly among graduate students engaged in demanding academic tasks. This study employed a descriptive quantitative research design to explore the level of academic procrastination among English language education master’s students, to identify academic areas are most prone to procrastination, and to investigate the reasons underlying this behavior. The study involved 48 graduate students enrolled in the English Language Education Master’s Program at Universitas Riau. Data were collected using the PASS questionnaire from Solomon & Rothblum (1984) that included sections on procrastination level, areas of procrastination, and reasons for procrastination. Descriptive analysis revealed that 67% of students exhibited moderate levels of procrastination, while 33% reported high levels. Writing tasks, such as thesis writing and preparing academic papers, emerged as the most frequently procrastinated area, followed by preparing for exams, reading assignments, and administrative tasks. The main reasons for procrastination included difficulty in time management, fear of making mistakes, lack of motivation, perfectionism, and challenges in balancing academic work with employment or personal responsibilities. These findings underscore the importance of addressing both the cognitive and emotional factors contributing to academic procrastination. Interventions that target time management skills and academic self-confidence may help reduce procrastination and improve graduate student performance.